Fatal Lymphoproliferative Disease in Two Siblings Lacking Functional FAAP24 - Daschkey, Svenja; Bienemann, Kirsten; Schuster, Volker; Kreth, Hans Wolfgang; Linka, Rene Martin; Hoenscheid, Andrea; Fritz, Gerhard; Johannes, Christian; Fleckenstein, Bernhard; Kempkes, Bettina; Gombert, Michael; Ginzel, Sebastian; et al. (Journal of Clinical Immunology, 2016)
Hereditary defects in several genes have been shown to disturb the normal immune response to EBV and to give rise to severe EBV-induced lymphoproliferation in the recent years. Nevertheless, in many patients, the molecular basis of fatal EBV infection still remains unclear. The Fanconi anemia-associated protein 24 (FAAP24) plays a dual role in DNA repair. By association with FANCM as component of the FA core complex, it recruits the FA core complex to damaged DNA. Additionally, FAAP24 has been shown to evoke ATR-mediated checkpoint responses independently of the FA core complex. By whole exome sequencing, we identified a homozygous missense mutation in the FAAP24 gene (cC635T, pT212M) in two siblings of a consanguineous Turkish family who died from an EBV-associated lymphoproliferative disease after infection with a variant EBV strain, expressing a previously unknown EBNA2 allele.In order to analyze the functionality of the variant FAAP24 allele, we used herpes virus saimiri-transformed patient T cells to test endogenous cellular FAAP24 functions that are known to be important in DNA damage control. We saw an impaired FANCD2 monoubiquitination as well as delayed checkpoint responses, especially affecting CHK1 phosphorylation in patient samples in comparison to healthy controls. The phenotype of this FAAP24 mutation might have been further accelerated by an EBV strain that harbors an EBNA2 allele with enhanced activities compared to the prototype laboratory strain B95.8. This is the first report of an FAAP24 loss of function mutation found in human patients with EBV-associated lymphoproliferation.
EVALuna2:8324